MENINGKATKAN PENGUASAAN PESERTA DIDIK TERHADAP MATERI SUMBER ENERGI LISTRIK DAN KEGUNAANNYA DENGAN METODE EKSPLORASI - sutrisno sutrisno (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The aim of this action research were to (1) describe the influence of exploration method in the Electric Energy Sources material and its use in science to improve the students’ learning outcomes and (2) know the influence of exploration method in the Electric Energy Sources material and its use in science to students’ motivation. This study was designed in a Classroom Action Research (PTK) within 3 cycles. Each cycle consisted of four stages, namely the action planning, action, observation/ measurement, and reflection/ retrieval conclusion. This object was the sixth graders student of state elementary school Weduni, Deket - Lamongan. The data obtained from tests and observation sheet of formative learning activities. After applying the method, learning outcomes in the first cycle is as much as 56%. In the second cycle learning outcomes increased to 70%, and increased again to 88.66% in the third cycle. The conclusion from this study was the exploration method can be a positive influence on learning outcomes and students’ motivation of state elementary school of Weduni, Deket - Lamongan.